Fabrication of ultrathin single-layer 2D metal–organic framework nanosheets with excellent adsorption performance via a facile exfoliation approach. Issue 1 (16th December 2020) - Liu, Lei-Lei; Chen, Jing; Zhang, Yan; Yu, Cai-Xia; Du, Wei; Sun, Xue-Qin; Zhang, Jiang-Lou; Hu, Fei-Long; Mi, Yan; Ma, Lu-Fang
Abstract : A single-layer of 2D metal–organic framework nanosheet was elaborately prepared by a facile exfoliation approach and showed unprecedented performance in removing congo red. Abstract : Achieving ultrathin two-dimensional (2D) metal–organic framework (MOF) nanosheets is an extremely meaningful topic and still remains a great challenge. Herein, for the first time, a single-layer 2D Zn-MOF nanosheet was obtained by a facile top-down strategy based on 3D layered Zn-MOF crystals. It involves two steps: firstly, weakening the van de Waals interactions between layers by the protonation of the Zn-MOF under acidic conditions; secondly, further destroying the weakened van der Waals interactions through electrostatic interactions using negatively charged tape molecules, congo red (CR) or methyl orange (MO). Transmission electron microscopy and atomic force microscopy studies demonstrated that ultrathin single-layer (3.4 nm) 2D Zn-MOF nanosheets were obtained, with an ultra-large lateral size ( ca. 6 μm), and showed unprecedented adsorption performance toward CR. For CR, the 2D Zn-MOF nanosheets could not only achieve record high uptake capacity (6639.55 mg g −1 ), but also present efficient and rapid removal. It is worth noting that the adsorption of CR could prevent restacking of the exfoliated 2D Zn-MOF nanosheets and facilitate further exfoliation, which in turn provided more 2D Zn-MOF nanosheets for CR adsorption. Moreover, CR can be selectively and efficiently removed even from the mixed dye solution with different charges. It is anticipated that this methodology could provide a concept to integrate exfoliation and pollutant removal into one process, fulfilling the facile synthesis of ultrathin functionalized 2D nanosheets, with high performance for pollutant removal.